Antibody and cytokine levels in visceral leishmaniasis patients with varied parasitemia before, during, and after treatment in patients admitted to Arba Minch General Hospital, southern Ethiopia. - Dagimawie Tadesse; Alemseged Abdissa; Mekidim Mekonnen; Tariku Belay; Asrat Hailu (Public Library of Science (PLoS), 2021)
Background Visceral leishmaniasis is a disease caused by disseminated Leishmania donovani infection which affects almost half a million people annually. Most of the patients are reported from the Indian sub-continent, Eastern Africa and Brazil. In this study, we aimed to determine the levels of antibodies and cytokines in visceral leishmaniasis patients and to examine associations of parasitemia with the clinical states of patients. A prospective study was carried out, enrolling a total of 48 active VL patients who were evaluated before, during different time points and, three months after treatment. Serum cytokine concentrations, antibody levels, parasitemia, laboratory (hematologic and biochemical) measurements, and clinical parameters were assessed. Results Counts of WBC and platelets, and measurements of hemoglobin (Hb) increased during treatment (P ≤ 0.05). Elevated levels of circulating IL-10, IFN-γ, and TGF-β1 were measured before treatment. The observed increase in serum IL-10 remarkably declined within 7 days after the start of treatment. Anti-leishmanial antibody index (AI) was high in all VL patients irrespective of spleen aspirate parasite grade before treatment and at different times during treatment. However, a significant (P ≤ 0.05) decrease of AI was observed 120 days post-treatment. IL-2 serum levels were below the detection limit at all sampling points. Conclusions The present results suggest that IL-10, IFN-γ, and TGF-β1 can be used as markers of active visceral leishmaniasis. In addition, measuring circulating cytokines concentrations, particularly IL-10, in combination with other clinical evaluations, could be used as criteria for the cure. The observation that a high serum concentration of IFN-gamma at baseline was associated with low parasitemia deserves further investigations.